Os caminhos do terrorismo e da desumanização e o encontro de um denominador comum através da cooperação internacional - Bastos, Bruna (2021)
Ideological-religious terrorism is a global phenomenon that gained new shapes after September 11th, 2001, becoming a movement that, just like internet and globalization, ignores national boundaries and affects, direct or indirectly, all forms of society. This species of terrorism has a big connection to Islamic culture, representing a small part of this community that manifests, illegitimately, against the oppressions typical of a globalization that privileged only the economic aspects, while affected all the other areas of social life. The “war against terror”, deflagrated in 2003 with the Iraqi’s invasion by United States of America, clearly didn’t serve to its purposes of global peace and ending the terrorist threat, because this phenomenon spread worldwide, reaching other locations through new Salafist groups and showing that it’s not possible to end derived violence with structural violence. Besides, dehumanizing speeches directed to Orient and to Muslim community instigate this panorama, avoiding that groups of people can be seen and human beings and, consequently, as rights owner. Therefore, the objective of this work is to verify is international cooperation can be a common denominator to search for non-violent forms to fight terrorism, going through the rejection of dehumanizing speeches. So, it may be asked: is it possible to think an international cooperation that’s enough to develop an effective and humanized combat to terrorism, going through the recognition of human rights to social groups that were taken from their human condition? The study uses the hypothetical-deductive approach method, starting with wide conceptions about terrorism and dehumanizing speeches in order to head the study to the treatment given by media and countries to this phenomenon, making possible to think an international cooperation to solve the problem. The procedure methods are the monographic and typological, through bibliographical and documental researches. The following dissertation was divided in two chapters, and the first one is responsible for studying the phenomenon of ideological-religious terrorism under the leaning of cultural studies, understanding its link with cultural identities, and verify which way the treatment given by countries and media spread scenarios of cultural hierarchy in international environment. The second chapter, by its turn, approaches the dehumanizing speeches by trying to comprehend how they occur, what are its consequences and in which way they are connected to power relations that are built in global scenario, going through international cooperation as a possibility of human and non-violent combat to terrorism. It is possible to conclude that international cooperation is a good alternative to an effective and humanized to combat terrorism, because it takes care of cultural inclusion and human rights effectiveness, approaching all areas of social life in a cooperative strategy; however, this possibility is blocked by the lack of interest of countries, which why it must be looked for new ideas to combat terrorism.